The effect of emotional intelligence on employees’ performance / Nur Fhatin Adillah Mat Azalan - Mat Azalan, Nur Fhatin Adillah (Faculty of Business and Management, 2018)
This research paper involves the investigation on the impact of Emotional Intelligence on Employees’ Performance. The competencies of Emotional Intelligence studied were self-awareness, self-management, social awareness and relationship management. Data collected were from a convenient sample size of 306 employees in Petrolium Nasional Berhad (Petronas).